2016
DOI: 10.1007/s00262-016-1878-6
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of mouse breast adenocarcinoma growth by ablation with intratumoral alpha-irradiation combined with inhibitors of immunosuppression and CpG

Abstract: It has been demonstrated that aggressive in situ tumor destruction (ablation) could lead to the release of tumor antigens, which can stimulate anti-tumor immune responses. We developed an innovative method of tumor ablation based on intratumoral alpha-irradiation, diffusing alpha-emitters radiation therapy (DaRT), which efficiently ablates local tumors and enhances anti-tumor immunity. In this study, we investigated the anti-tumor potency of a treatment strategy, which combines DaRT tumor ablation with two app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 40 publications
2
29
0
Order By: Relevance
“…Sildenafil was also used as an adjuvant in an in vivo study of an experimental local tumour ablation modality DaRT (diffusing alpha-emitters radiation therapy) [ 34 ]. As with many local ablative therapies, there is some evidence that DaRT can initiate a systemic anti-tumour immune response (abscopal effects) via the release of tumour antigens during local tumour tissue destruction.…”
Section: Pre-clinical Evidence In Cancer— In Vitro mentioning
confidence: 99%
“…Sildenafil was also used as an adjuvant in an in vivo study of an experimental local tumour ablation modality DaRT (diffusing alpha-emitters radiation therapy) [ 34 ]. As with many local ablative therapies, there is some evidence that DaRT can initiate a systemic anti-tumour immune response (abscopal effects) via the release of tumour antigens during local tumour tissue destruction.…”
Section: Pre-clinical Evidence In Cancer— In Vitro mentioning
confidence: 99%
“…Phosphodiesterase 5A (PDE5A) inhibitors including sildenafil, tadalafil, and vardenafil have also been shown to boost anticancer immune responses by depleting MDSCs . Accordingly, the combined depletion of tumor‐infiltrating T REG cells (with metronomic cyclophosphamide) and circulating MDSCs (with sildenafil) ameliorated the therapeutic activity of diffusing alpha‐emitters RT plus CpG oligodeoxynucleotides (a TLR9 agonist) in a mouse model of breast cancer . Finally, bortezomib (a proteasome inhibitor currently approved for the treatment of multiple myeloma) improved the ability of a single RT dose of 5 Gy to increase the levels of multiple death receptors on the membrane of mouse colorectal carcinoma SW620 cells, hence exacerbating their sensitivity to CTL‐mediated killing .…”
Section: Strategies To Improve Immunostimulationmentioning
confidence: 99%
“…Moreover, there are some concerns on the use of these agents linked to impaired T‐cell maintenance and effector memory T‐cell differentiation . Finally, multiple TLR agonists have been shown to synergize with RT in various preclinical tumor models, at least in part as they boosted type I IFN responses that are required for optimal RT‐driven anticancer immunity . Although this latter approach is not specifically designed to reverse RT‐driven immunosuppression, general immunostimulatory interventions including TLR agonists and some cytokines may be promising tools to exacerbate the immunostimulatory potential of RT in the clinics.…”
Section: Strategies To Improve Immunostimulationmentioning
confidence: 99%
“…Preclinical studies have suggested that DaRT therapy may be employed to harness the immune response when used in conjunction with immunotherapy. 12,13 One patient in this report experienced an immune repose with reduced disease at other tumor sites concomitant with treatment of 1 of the symptomatic lesions with DaRT therapy in the absence of any other therapy. In selected tumors with oligometastases, the use of DaRT targeted to a lesion in conjunction with immunotherapy could further augment the immune response compared with immunotherapy alone; trials are currently in development to test this hypothesis.…”
Section: Months After Dart Insertionmentioning
confidence: 86%